Effect of graphene oxide on thermal stability of aerogel bio-nanocomposite from cellulose-based waste biomass - Sinyee Gan; Sarani Zakaria; Chin Hua Chia; Hatika Kaco (Springer Netherlands, 2024)
By combining the waste of oil palm empty fruit bunch (EFB) and graphene oxide (GO), a GO/cellulose aerogel bio-nanocomposite was produced via a simple mixing method. The thermal properties of this nanocomposite were examined using thermogravimetric analysis (TGA), and the GO/cellulose aerogel bio-nanocomposite exhibited good thermal stability indicated by a delay in the degradation of the nanocomposite even at low GO incorporation. Experimental and modeled TGA curves were compared. The morphology of the GO/cellulose aerogel composite was observed under field emission scanning electron microscope. In GO/cellulose aerogel composite with 4 wt% GO, the pore volume and porosity decreased by more than 50% compared to aerogel without GO, and the density of the 4 wt% GO/cellulose aerogel composite showed a onefold increase compared with the pure cellulose aerogel. The degree of swelling and equilibrium-swelling ratio of regenerated GO/cellulose hydrogel and aerogel decreased with the higher GO concentration. The phase transition from EFB to regenerated GO/cellulose aerogel composite was evaluated using X-ray diffraction. This study has provided a simple pathway to produce environmentally friendly biocomposite materials.